Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1292/jvms.23-0038
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation effects of fetal and lactational exposure to the neonicotinoid pesticide clothianidin on the immune system and gut microbiota

Abstract: Recently, the effects of exposure to clothianidin (CLO) on the thymus and gut microbiota have become clear, but no report has examined its next-generation impacts. Pregnant C57BL/6N mice were administered a no-observed-adverse-effect-level dose of CLO until weaning. We examined CLO's effects on the gut microbiota and immune organs of dams and their 3-and 10-week-old male offspring. CLO administration led to several alterations of the top 30 bacterial genera in the gut microbiota in dams and 3-week-old mice. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 58 publications
(82 reference statements)
0
7
0
Order By: Relevance
“…Subsequently, questions arose about the reproductive toxicity of NNs [ 17 , 21 , 25 , 47 , 53 ], their neurotoxicity and involvement in cognitive‒emotional alterations [ 14 , 16 , 17 , 18 , 20 , 26 , 27 , 33 , 44 , 45 , 55 ], and their safety, even at the no-observed-adverse-effect level (NOAEL). Recently, subchronic exposure to clothianidin (CLO), a type of NN, has been reported to disrupt the intestinal microbiota of rats [ 35 ] and mice [ 30 , 56 ]. CLO may affect the host via dysbiosis, as reduced diversity of the gut microbiota (dysbiosis) is associated with immunomodulatory dysfunction [ 37 ] and neurological disorders [ 4 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, questions arose about the reproductive toxicity of NNs [ 17 , 21 , 25 , 47 , 53 ], their neurotoxicity and involvement in cognitive‒emotional alterations [ 14 , 16 , 17 , 18 , 20 , 26 , 27 , 33 , 44 , 45 , 55 ], and their safety, even at the no-observed-adverse-effect level (NOAEL). Recently, subchronic exposure to clothianidin (CLO), a type of NN, has been reported to disrupt the intestinal microbiota of rats [ 35 ] and mice [ 30 , 56 ]. CLO may affect the host via dysbiosis, as reduced diversity of the gut microbiota (dysbiosis) is associated with immunomodulatory dysfunction [ 37 ] and neurological disorders [ 4 ].…”
mentioning
confidence: 99%
“…Cecal contents were stored at −80°C until 16S rRNA analysis and cryptdin-1 (Crp1, a major α-defensin in mice) quantification. The 16S rRNA analysis was performed as previously reported [ 30 ]. Briefly, a nucleic acid purification system (Maxwell ® RSC; Promega K.K., Tokyo, Japan) and a nucleic acid purification kit (Maxwell ® RSC Fecal Microbiome DNA Kit [AS 1700]; Promega K.K.)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous reports indicate the involvement of α7 nAChR in the regulation of anti-inflammatory responses, with its expression observed in macrophages, T cells, B cells, mast cells, and so on [See Review 19]. Previous studies showed that exposure to clothianidin (CLO), a class of NNs, causes a decrease in rat thymus weight [ 15 ], an increase in Hassall bodies in mouse thymus [ 13 ], and dysbiosis of the intestinal microbiota [ 13 , 15 , 24 ]. It has been shown that an imbalance of the intestinal microbiota causes allergies [See Review 18 ], raising the possibility that NNs may disrupt the immune system and contribute to the development of allergic diseases.…”
mentioning
confidence: 99%
“…In 2012, however, Kimura-Kuroda reported that the NNs imidacloprid (IMI) and acetamiprid (ACE) induce nAChR-mediated neuronal excitation in the cerebellar neurons of newborn rats, and it has become clear that NNs may have adverse effects on human health, especially on the developing brain [ 18 ]. Recently it was reported that birds and mammals exposed to no-observed-adverse-effect levels (NOAELs) of NNs exhibit toxic effects on reproduction, the thymus, gut microbiota, and neurobehavior [ 4 , 9 , 10 , 11 , 13 , 19 , 24 , 27 , 29 , 31 , 36 , 43 , 50 ]. In addition, NNs were detected in the urine of adults, children, and newborns [ 15 , 16 , 32 , 45 ].…”
mentioning
confidence: 99%